2023
DOI: 10.3390/ijerph20054664
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Perceived Mental Load and Motor Performance during Practice-to-Learn and Practice-to-Maintain in Basketball

Abstract: Background: Attentional resource allocation during sports practice is associated with the players’ perceived mental load. However, few ecological studies address this problem by considering the players’ characteristics (e.g., practice experience, skill and cognition). Therefore, this study aimed to analyse the dose-response effect of two different types of practice, each with different learning objectives, on mental load and motor performance by using a linear mixed model analysis. Method: Forty-four universit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 83 publications
0
0
1
Order By: Relevance
“…Specifically, all the variables presented higher values in away matches when compared to home ones (Cognitive load, 7.49 vs. 7.17; Emotional load, 7.39 vs. 7.02; Affective load, 7.44 vs. 7.08). These results seem understandable, as it has been shown previously a clear relationship between increases in perceived mental load and more demanding contexts [43]; however, these higher mental load values are not consistent for all match outcomes in our study. Several authors have reported that cognitive load is related to the emotional state of the athletes and teams [44], which is sustainable with our results; in a positive context (i.e., win at home), players show lower mental load values (i.e., all variables in this study).…”
Section: Internal Load Variablescontrasting
confidence: 97%
“…Specifically, all the variables presented higher values in away matches when compared to home ones (Cognitive load, 7.49 vs. 7.17; Emotional load, 7.39 vs. 7.02; Affective load, 7.44 vs. 7.08). These results seem understandable, as it has been shown previously a clear relationship between increases in perceived mental load and more demanding contexts [43]; however, these higher mental load values are not consistent for all match outcomes in our study. Several authors have reported that cognitive load is related to the emotional state of the athletes and teams [44], which is sustainable with our results; in a positive context (i.e., win at home), players show lower mental load values (i.e., all variables in this study).…”
Section: Internal Load Variablescontrasting
confidence: 97%
“…The results showed the moderating effect of playing experience in attenuating the effect of increasing task difficulty on inhibitory control. Those players with more experience perceived fewer mental demands (Gutiérrez-Capote et al, 2023), translating into better results in their cognitive performance in the RES. Within the context of the optimal challenge framework, it is established that the functional difficulty of a task, in addition to being affected by experience and practice conditions, also depends on individual processing characteristics (Guadagnoli and Lee, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The methodology used in the present study has been previously employed and documented (Gutiérrez-Capote et al, 2023). In that study, it was reported that players experienced an increase in perceived mental load and a decrease in motor performance under conditions involving practice variability and imposed restrictions.…”
Section: The Rationale For the Current Designmentioning
confidence: 99%
See 1 more Smart Citation